An apical hypoxic niche sets the pace of shoot meristem activity - Weits, Daan; Gaillochet, Christophe; Lohmann, Jan U. (Nature, 2019)
Hypoxia in the shoot meristem of Arabidopsis links the regulation of metabolic activity to development by inhibiting proteolysis of a substrate of the N-degron pathway, which controls class-III homeodomain-leucine zipper transcription factors.